Pendampingan Digitalisasi Marketing dan Legalitas Usaha UMKM untuk Meningkatkan Mengembangkan UMKM Desa Banjaragung Kecamatan Bareng Jombang Jawa Timur - Dzikri Kurniawan; Naila Aisyah Putri; Sheily Novitasari; Siti Hawa’ Octaviani; Mu’tasim Billah; Zawawi Zawawi (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Group 02 KKN-T MBKM UPN "Veteran" East Java located in Banjaragung Village, Bareng District, Jombang Regency provided assistance on digital marketing and business legality to improve the quality of MSME (Micro, Small, and Medium Enterprises) products. There are still many MSMEs in Banjaragung Village that do not have NIB, are halal certified, and also don’t take advantage of the current digital marketing. The purpose of this service activity is to improve the development of MSMEs in Banjaragung Village, Bareng District, Jombang Regency through digital marketing assistance and MSME business legality. The assistance program for making digital marketing includes making social media such as Instagram Business, e-commerce Shopee and Tokopedia, making stickers for new packaging, and making banners for MSMEs. Business legal assistance in the form of assistance provided by the group 02 KKN-T MBKM in the manufacturing process, as well as collecting various data needed to meet the requirements for making NIB and Halal Certification. With assistance regarding digital marketing and business legality, this business is able to expand market reach and increase consumer confidence in the products being marketed, so that it is able to achieve the goals expected of MSME players in Banjaragung Village.